Impact of order of fixed-ratio presentation on demand for self-administered remifentanil in male rats. Issue 2 (April 2020) - Maguire, David R.; Minervini, Vanessa; Dodda, Vikas; France, Charles P.
Abstract : The behavioral economics framework has been used extensively to study factors that control operant behavior, including quantification of reinforcing effectiveness of drugs of abuse. Generally, consumption of a commodity decreases with increasing price, and the rate of decrease reflects demand elasticity, which is inversely related to reinforcing effectiveness. Drugs with low elasticity have greater effectiveness than those with greater elasticity. Price is often manipulated by varying the number of responses required to obtain an infusion (e.g. fixed ratio schedule); however, many studies present the fixed ratio in only one order (usually ascending), which could introduce sequence effects that influence estimates of demand. This study examined the impact of the order of fixed ratio presentation on demand for the mu opioid receptor agonist remifentanil (0.0032 mg/kg/infusion) using an ascending and a mixed order of fixed ratio presentation. Seven male rats lever pressed for intravenous infusions. The fixed ratio varied across 3-session blocks, yielding a demand curve. During the first and third phases, the fixed ratio increased, and, during the second phase, fixed ratio values were presented in a mixed order. On average, rats obtained more than 60 infusions per session under baseline (fixed ratio 1) during the each of the three phases, with the number of infusions received decreasing progressively with increasing fixed ratio values. Estimates of elasticity across the three phases were not statistically different indicating that the order of fixed ratio presentation did not markedly alter estimates of demand and further demonstrating the robustness of price as a source of control over operant behavior, including behavior maintained by drug reinforcers.